Sensor-driven recording and annotation of dry slope jumps - Verstockt, S.; De Bock, T.; De Bock, J.; Decorte, R.; Vanhaeverbeke, J.; Slembrouck, M. (9th International Congress on Science and Skiing, March 18 - 22, 2023, Saalbach-Hinterglemm, Austria, 2023)
INTRODUCTION: In order to facilitate the work of coaches and to ease the creation of personalized stories (that athletes can easily share on their social media accounts) we are developing a sensor-driven methodology to automatically record and annotate jumps at the dry slope of Sport Vlaanderen in Genk, Flanders, Belgium 1.